Using Wattpad to Promote the Students’ Responses to Literary Works: EFL College Students’ Perspectives and Experiences of Enjoying Short Stories - Mega Anggitasari; Wawan Tarwana; R. Bunga Febriani; Syafryadin Syafryadin (Yayasan Karinosseff Muda Indonesia, 2020)
This research is to investigate how EFL college students response in enjoying short stories by using Wattpad and to find out how their perception and experiences in enjoying short stories by means reading Wattpad. As interest in literacy activities, EFL college students’ choose Wattpad as an application to read short stories, Wattpad is a fairly popular and efficient application for reading short stories and can provide comments directly within the short story paragraphs and Wattpad has many advantages in promoting reader-response theory to EFL college students’ .This case study was conducted to the college students and 40 students. Three instruments covering the observation, the interview, and the questionnaire were chosen to gain the data. It was concluded that there is the positive feedback of using Wattpad as a media to learning literature similar to those previous studies, this research also focuses on Wattpad as a media to learning literature.